Carboxypeptidase U (CPU, carboxypeptidase B2, activated thrombin‐activatable fibrinolysis inhibitor) inhibition stimulates the fibrinolytic rate in different in vitro models. (30th August 2018) - Leenaerts, D.; Loyau, S.; Mertens, J. C.; Boisseau, W.; Michel, J. B.; Lambeir, A. M.; Jandrot‐Perrus, M.; Hendriks, D.
Abstract : Essentials AZD9684 is a potent inhibitor of carboxypeptidase U (CPU, TAFIa, CPB2). The effect of AZD9684 on fibrinolysis was investigated in four in vitro systems. The CPU system also attenuates fibrinolysis in more advanced hemostatic systems. The size of the observed effect on fibrinolysis is dependent on the exact experimental conditions. Summary: Background: Carboxypeptidase U (CPU, carboxypeptidase B2, activated thrombin‐activatable fibrinolysis inhibitor) is a basic carboxypeptidase that attenuates fibrinolysis. This characteristic has raised interest in the scientific community and pharmaceutical industry for the development of inhibitors as profibrinolytic agents. Objectives: Little is known about the contribution of CPU to clot resistance in more advanced hemostatic models, which include blood cells and shear stress. The aim of this study was to evaluate the effects of the CPU system in in vitro systems for fibrinolysis with different grades of complexity. Methods: The contribution of the CPU system was evaluated in the following systems: (i) plasma clot lysis; (ii) rotational thromboelastometry (ROTEM) in whole blood; (iii) front lysis with confocal microscopy in platelet‐free and platelet‐rich plasma; and (iv) a microfluidic system with whole blood under arterial shear stress. Experiments were carried out in the presence or absence of AZD9684, a specific CPU inhibitor. Results: During plasma clot lysis, addition of AZD9684 resulted in 33% faster lysis. In ROTEM, the lysis onset time was decreased by 38%. For both clot lysis and ROTEM, an AZD9684 dose‐dependent response was observed. CPU inhibition in front lysis experiments resulted in 47% and 50% faster lysis for platelet‐free plasma and platelet‐rich plasma, respectively. Finally, a tendency for faster lysis was observed only in the microfluidic system when AZD9684 was added. Conclusions: Overall, these experiments provide novel evidence that the CPU system can also modulate fibrinolysis in more advanced hemostatic systems. The extent of the effects appears to be dependent upon the exact experimental conditions.